The Needs and Availability Analysis of Clean Water in The Mebidang Spam Services in Medan Marelan Region - Muhammad, Faathir; Malau, Flaura Dearnita; Gultom, Natalia Cindy Octavia; Lubis, Putri Nabila; Arisetyo, Rama; Mulyana, Rachmat; Wardana, Novrizaldi (Journal of Green Science and Technology, 2025)
Analysis of clean water needs and availability in Medan Marelan District is needed to ensure the adequacy of SPAM services along with population growth and increasing domestic and non-domestic water consumption in the future. This study aims to identify the projection of clean water needs and availability that can be accessed by the community in Medan Marelan District over the next 10, 30, and 50 years. The analysis was conducted using a quantitative descriptive approach, utilizing secondary data sourced from relevant agencies and applying arithmetic projection methods to estimate population growth, as well as the increase in both domestic and non-domestic water demands. The calculation results show that the need for clean water in the area will increase significantly from 2024 to 2075, with a total need reaching 680.27 liters per second in 2075. However, the availability of clean water from the Mebidang Regional Drinking Water Supply System (SPAM), with a capacity of 1,100 liters per second, is estimated to still be able to meet these needs during the observed period. This surplus condition provides a strong basis for policy planning and sustainable water resource management in Medan Marelan District.